The Complexity of Interaction between Executive Board Gender Diversity and Financial Performance: A Panel Analysis Approach Based on Random Effects. (9th July 2022) - Bogdan, Victoria; Popa, Dorina-Nicoleta; Beleneşi, M.
Abstract : This study examined the influence of the executive board of directors' gender diversity on the financial performance of listed companies on the Bucharest Stock Exchange, for the period 2011 to 2019. The analysis of the composition and different characteristics of the board and the executive directors proved to be effective tools for corporate governance in countries with an emerging capital market. Therefore, a disclosure index on directors' characteristics was used to moderate the interaction between gender diversity and financial performance, based on the theoretical framework provided by upper echelon theory. The study contributes to the enrichment of the literature both by using the composite indicator built by applying the multiway PCA method on panel data to express financial performance and by designing the ten EGLS panel models involving five financial indicators and two proxies for gender diversity. The results showed that there is a positive impact of the proportion of women on the executive board of directors on financial performance, measured through the composite index, ROA, ROE, and SOL. A statistically significant impact of gender diversity on financial performance was found only for SOL, in the case of the Blau index. Also, using the random-effects model to perform the panel data analysis, the results showed that a higher executive board size can be associated with better financial performance measured through the composite index, ROA, ROE, and EPS. Practical implications are significant for the board of executives' composition, the complexity of the relationship with the board, and reshaping governance practices.